Culinary in LSSR: Aspirations and Possibilities - Misevičius, Džiugas (Lietuvos istorijos studijos, 2020)
The aim of the thesis is to present a synthetized and organically structured image of Soviet Lithuanian culinary, which separately exists in contemporary historiography, Soviet archival documents and publications and in the memory of witnesses of that time. The paper analyzes the origins of Soviet culinary policy and shows how theoretical attitudes to nutrition were implemented in practice; it also discusses eating culture of the “Soviet man” by showing what and how was cooked and eaten at the canteens, restaurants, cafes and at home (for everyday and for special occasions); it also reveals the differences and tensions between “public” and “private” culinary.